Exploring Mental State of the Head Chef on the Film the Menu (2022) - Dennis Apriliyanto; Irma Rahmawati (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2026)
Lacanian psychoanalysis is a framework that helps interpret the hidden subconscious meanings in a film’s story and the psychology of its characters. The Menu (2022) presents Chef Slowik not only as a villain, but also as a deeply disturbed individual who suffers from psychological problems, including psychopathic tendencies. He loses his original passion for cooking and can no longer express his identity or emotions through food. This failure to communicate with others through his dishes reflects Lacan’s idea of failed self-expression and gradually leads to Slowik’s psychological collapse. Using a descriptive qualitative approach, this study examines how Chef Slowik’s objet petit a represents his inner sense of lack and how it eventually turns into jouissance, functioning as a form of criticism toward the Symbolic Order represented by Hawthorne restaurant. The findings show that Slowik’s objet petit a appears through dialogue and objects in the film, and it is this desire that ultimately drives his actions, speech, and the dishes he serves to elite guests as a critique of the existing Symbolic Order.